Childhood obesity: Is it related to feeding type of the infant? - Ünsür, Emel; Akıcı, Narin; Kızmaz, Didem (Journal of Surgery and Medicine, 2020)
Aim: The prevalence of childhood obesity has risen currently, and the relationship between feeding types in the infancy period and childhood obesity remains controversial. It is aimed to investigate the impact of feeding practices in the first six months of life on early childhood obesity in exclusively breast-fed, exclusively formula-fed, and mixed (breast milk and formula) fed Turkish infants. Methods: This study was conducted in the Department of Pediatrics at Haydarpasa Numune Training and Research Hospital with 545 children aged between 2-5 years. We asked the parents various questions to determine the feeding patterns during infancy. Three groups were formed: Exclusively breastfeed, exclusively formula-fed and the mixed (breast milk and formula) fed group. Obesity rates were determined according to body mass index (BMI) and compared. Results: Among a total of 545 children, with a mean age of 3.4 years, there were 285 (52,3%) females. Evaluation based on BMI revealed that the obesity (≥95th percentile) rate was 8.8% and the percentage of overweight children was significantly higher in the only formula-fed group (28.2%) compared to those who were only breast-fed (16.8%) (P=0.009). Conclusions: Our findings showed that feeding the child exclusively with formula during the first six months of life may increase body weight during early childhood more than feeding solely breast milk. Therefore, it is necessary to promote breastfeeding to prevent childhood obesity.